2008
DOI: 10.1242/jcs.026559
|View full text |Cite
|
Sign up to set email alerts
|

yuri gagarinis required for actin, tubulin and basal body functions inDrosophilaspermatogenesis

Abstract: A unique feature of the genus Drosophila is the formation of unusually long sperm tails. Sperm lengths of millimeters are common within this group, with the 1.8 mm sperm of D. melanogaster being fairly typical. This marked expansion in sperm length reflects an unusual aspect of spermatogenesis in these organisms: in contrast to other species in which an intraflagellar transport system is used for growth of the sperm flagellum (Scholey, 2006), Drosophila sperm axonemes are assembled in syncytial cysts by a mech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
72
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(78 citation statements)
references
References 32 publications
(38 reference statements)
6
72
0
Order By: Relevance
“…Although no direct demonstration has been done using immuno-EM on g-tubulin during spermatogenesis, g-tubulin staining shows a remarkably close correlation with the morphogenesis of CA, therefore it is accepted that it most likely represents the centriolar adjunct (Wilson et al 1997;Callaini et al 1999;Baker et al 2004;Texada et al 2008). In early spermatids, g-tubulin labels the vicinity of the giant centriole along most of its length ( Figure 2C).…”
Section: Resultsmentioning
confidence: 99%
“…Although no direct demonstration has been done using immuno-EM on g-tubulin during spermatogenesis, g-tubulin staining shows a remarkably close correlation with the morphogenesis of CA, therefore it is accepted that it most likely represents the centriolar adjunct (Wilson et al 1997;Callaini et al 1999;Baker et al 2004;Texada et al 2008). In early spermatids, g-tubulin labels the vicinity of the giant centriole along most of its length ( Figure 2C).…”
Section: Resultsmentioning
confidence: 99%
“…Instead, we have shown that the coiled-coil cytoplasmic protein Yuri Gagarin (Armstrong et al, 2006;Texada et al, 2008) is an essential component of the Spag4-BB anchoring mechanism, and that regulation of dynein-dynactin localization by Spag4 has a role in the process.…”
Section: Introductionmentioning
confidence: 90%
“…) and for Yuri nuclear localization (Texada et al, 2008). yuri is a complex locus encoding three major classes of ubiquitously expressed isoforms.…”
Section: F64mentioning
confidence: 99%
See 1 more Smart Citation
“…4B,C). This phenotype is reminiscent of mutants in the testis-specific proteasome subunit Prosα6T (Zhong and Belote 2007) or yuri (Texada et al 2008).…”
Section: Systematic Identification Of Testis-associated Lncrnas In Drmentioning
confidence: 99%